Protective integration and security policy coordination: comparing the SCO and CSTO - Allison, R (Oxford University Press, 2018)
This article contributes to research on non-Western regionalism by examining the function of security policy coordination in two macro-regional organisations in Eurasia, which include the primary non-Western powers: the Shanghai Cooperation Organisation (SCO)—with China and Russia—and the Collective Security Treaty Organisation (CSTO)—with Russia. The SCO has wider formal functions, and the CSTO is more hierarchical in practice, but both claim to be regional security providers with a focus on Central Asia. It is puzzling that Member States stress the importance of these organisations, that there have been regular meetings for over 15 years, yet their functionality is low judging by their ability to implement various ambitious projects. This article offers the explanation for this in the focus of SCO and CSTO Member State leaders on the interaction between domestic political, and regional security priorities. As a result, these bodies express the phenomenon of ‘protective integration’. It is a phenomenon that does not offer substantive regional integration or emphasise collective-action problem solving. It is intended to be sovereignty enhancing and to bolster regime security, stability, and legitimacy. It fosters a culture of interaction, normative bonding, and collective political solidarity. This is confirmed in empirical analysis of SCO and CSTO discourse and agreements over counter-terrorism, information security, and foreign policy coordination. However, the bonds of protective integration have weakened as separatism has become a divisive issue since 2014 over Russian action in Ukraine. Moreover, organisational enlargement of the SCO further threatens its cohesion, while it is being displaced by the belt and road initiative in the wider context of Chinese foreign and economic policy priorities. Neither the SCO nor the CSTO are likely to be dissolved, but their purposes are likely to become more diffuse.